2016
DOI: 10.1007/s10237-016-0860-8
|View full text |Cite
|
Sign up to set email alerts
|

On the characterization of the heterogeneous mechanical response of human brain tissue

Abstract: The mechanical characterization of brain tissue is a complex task that scientists have tried to accomplish for over 50 years. The results in the literature often differ by orders of magnitude because of the lack of a standard testing protocol. Different testing conditions (including humidity, temperature, strain rate), the methodology adopted, and the variety of the species analysed are all potential sources of discrepancies in the measurements. In this work, we present a rigorous experimental investigation on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
104
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(113 citation statements)
references
References 62 publications
6
104
3
Order By: Relevance
“…In quantitative terms, it is interesting to note that, converting the averaged values of E obtained in our measurements ( Fig. 2a) to shear moduli G by dividing E by 2(1+ν) (where ν = 0.5 is the Poisson's ratio of compressibility), one obtains values for G of 0.5-0.8±0.1 kPa, which is in good agreement with macroscopic (i.e., not localized) frequency sweep measurements reported in the literature [28,31,[50][51][52][53][54][55][56]. A direct comparison with other local measurements is unfortunately not possible, because the latter have been either performed on different kind of samples (different age, species, slicing direction) or under very diverse indentation stroke protocols, which, because of the highly viscoelastic behavior of the material, give rise to very different results [23-26, 29, 33-36, 57].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In quantitative terms, it is interesting to note that, converting the averaged values of E obtained in our measurements ( Fig. 2a) to shear moduli G by dividing E by 2(1+ν) (where ν = 0.5 is the Poisson's ratio of compressibility), one obtains values for G of 0.5-0.8±0.1 kPa, which is in good agreement with macroscopic (i.e., not localized) frequency sweep measurements reported in the literature [28,31,[50][51][52][53][54][55][56]. A direct comparison with other local measurements is unfortunately not possible, because the latter have been either performed on different kind of samples (different age, species, slicing direction) or under very diverse indentation stroke protocols, which, because of the highly viscoelastic behavior of the material, give rise to very different results [23-26, 29, 33-36, 57].…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies on brain mechanics have been mainly limited to the comparison between white and gray matter, with results that are either inconsistent or lack quantitative structure analysis [23][24][25][26][27][28][29][30][31]. Only recently, one study has shown that the mechanical properties correlate with myelin content in bovine brain [24], while stiffness was found to scale with the cell nucleus area in spinal cord of mouse and retinal ruminant tissue [30,32].…”
mentioning
confidence: 99%
“…Figures 11 and 12 illustrate that brain tissue not only stiffens with increasing strain but also with increasing strain rate. Rate-dependence of brain stiffness has consistently been reported in the literature using different testing techniques: shear testing or oscillatory shear testing [44,127,151], uniaxial compression or tension [57,83,85,132,137,140], indentation [20,107,136,163], and magnetic resonance elastography [36,145]. Figure 11 illustrates uniaxial compression, tension, and simple shear experiments performed at strain rates of 0.33 and 0.0067 1/s, respectively.…”
Section: Brain Stiffness Increases With Increasing Strain Ratementioning
confidence: 78%
“…It is known that the brain has a rate-dependent behavior and gets stiffer by increasing the loading rate [16,59]. That is why, in literature, it is common to conduct in vitro tests with certain strain rates to capture the wider properties of the brain [18,19,60]. Similar approaches have been applied to identify the material parameters of brainstem, dura, and other rate-dependent biological tissue [31,61].…”
Section: Discussionmentioning
confidence: 99%